2001
DOI: 10.1063/1.1420486
|View full text |Cite
|
Sign up to set email alerts
|

Single-simulation determination of phase boundaries: A dynamic Clausius–Clapeyron integration method

Abstract: We present a dynamic implementation of the Clausius–Clapeyron integration (CCI) method for mapping out phase-coexistence boundaries through a single atomistic simulation run. In contrast to previous implementations, where the reversible path of coexistence conditions is generated from a series of independent equilibrium simulations, dynamic Clausius–Clapeyron integration (d-CCI) explores an entire coexistence boundary in a single nonequilibrium simulation. The method gives accurately the melting curve for a sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 32 publications
2
53
0
Order By: Relevance
“…The methods continue to be developed, and there is much recent literature on this topic [24,[26][27][28]83]. Several of the approaches utilize variations of the Gibbs-Duhem relationship [24,[26][27][28].…”
Section: Equilibrium Behavior: Melting Curves and Phase Diagrams Intementioning
confidence: 98%
See 2 more Smart Citations
“…The methods continue to be developed, and there is much recent literature on this topic [24,[26][27][28]83]. Several of the approaches utilize variations of the Gibbs-Duhem relationship [24,[26][27][28].…”
Section: Equilibrium Behavior: Melting Curves and Phase Diagrams Intementioning
confidence: 98%
“…Several of the approaches utilize variations of the Gibbs-Duhem relationship [24,[26][27][28]. A more direct approach is to use perturbation from hard-sphere systems, utilizing the Weeks-Chandler-Anderson (WCA) [84,85] approach.…”
Section: Equilibrium Behavior: Melting Curves and Phase Diagrams Intementioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Experimentally, it has been observed that the melting of crystalline materials is facilitated by introducing heterogeneous nucleation sites at the surface of the solid. [3][4][5] By suppressing surface nucleation, melting must occur by homogeneous nucleation in the bulk solid and it becomes possible to superheat the crystal.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 These authors have shown that the AS technique can also be used to evaluate the free energy not at a single temperature, but in a predefined temperature range. They first showed that, in terms of the free energy, there is an exact equivalence between changing the temperature while keeping the potential energy function fixed, and fixing the temperature while scaling the potential.…”
Section: Introductionmentioning
confidence: 99%